2019
DOI: 10.1016/j.drugalcdep.2019.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Resiliency factors that protect against post-deployment drug use among male US Army Reserve and National Guard soldiers

Abstract: Background: Service members who have been deployed are at risk for substance use, especially Reserve/Guard troops. However, it is unclear what modifiable factors protect against substance use in this at-risk population. Our objective was to examine the effects of pre-, peri-, and postdeployment resiliency factors on post-deployment drug use. Methods: Data were drawn from Operation: SAFETY (Soldiers and Families Excelling Through the Years), an ongoing study examining the health of US Army Reserve/National Guar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
5
0
1
Order By: Relevance
“…Recent research in adolescent populations has shown that a lower sense of belonging is associated with greater approval and use of substances (Bakhtiari et al., 2020). Further, our prior work showed that soldiers with greater perceived social support from their military units were less likely to report post‐deployment drug use (Hoopsick, Benson, et al., 2019) and problems with mental health (Hoopsick, Homish, Collins, et al., 2021). Taken together with the findings of the current study, it is possible that non‐deployment might act as an ecological stressor to affect never‐deployed soldiers' propensity for substance use.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Recent research in adolescent populations has shown that a lower sense of belonging is associated with greater approval and use of substances (Bakhtiari et al., 2020). Further, our prior work showed that soldiers with greater perceived social support from their military units were less likely to report post‐deployment drug use (Hoopsick, Benson, et al., 2019) and problems with mental health (Hoopsick, Homish, Collins, et al., 2021). Taken together with the findings of the current study, it is possible that non‐deployment might act as an ecological stressor to affect never‐deployed soldiers' propensity for substance use.…”
Section: Discussionmentioning
confidence: 97%
“…It is also possible that the social components of these negative emotions, including a loss of connectedness and camaraderie with soldiers' units due to non-deployment, may affect soldiers' psychosocial well-being. Among USAR/NG soldiers who were deployed, greater perceived social support from their military unit members during the deployment period was associated with a lower likelihood of post-deployment drug use (Hoopsick, Benson, et al, 2019). Social support from one's unit has also been associated with less mental health symptomatology among both previously-deployed and neverdeployed USAR/NG (Hoopsick, Homish, Collins, et al, 2021).…”
Section: Non-deploymentmentioning
confidence: 94%
See 1 more Smart Citation
“…The potential for IIR to foster strong social connections for veterans is significant because strong interpersonal relationships and social support predict resilience among veterans (Hoopsick et al, 2019; Kelley et al, 2017; Welsh et al, 2015) and their family members (Bowen et al, 2003; Russo & Fallon, 2015; Sheppard et al, 2010). In fact, social support is one of the most significant predictors of the development and course of posttraumatic stress (Charuvastra & Cloitre, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Дослідники Hoopsick, Benson, Homish, Homish [34] оцінили такі потенційно захисні фактори щодо вживання наркотиків, як наявність підготовки до відряджень, підтримка підрозділу, підтримка родини / друзів під час останнього розгортання, задоволеність шлюбом. Було встановлено, що підтримка підрозділу (р ≤ 0,05), підтримка родини / друзів під час розгортань (р ≤ 0,05) були пов'язані із більш низькою ймовірністю вживання наркотиків з урахуванням віку, звання, вислуги, бойового впливу, черепно-мозкових травм, часу з моменту останнього відрядження до бойової зони та вихідного рівня вживання наркотиків.…”
Section: постановкаunclassified